Investigating the properties of medium density fiberboard from licorice root residues - Ahmad reza Zahedi tabarstani (تحقیقات علوم چوب و کاغذ ایران, 2012)
Licorice root residue, a non wood lignocelullosic raw material produced  following extraction process was investigated for medium density fiberboard production. MDF was produced utilizing fiber generated applying three steaming times (15, 20 and 25 minutes) at 170 °C steam temperature.   The fibers were blended with 10 or 12 % urea formaldehyde resin and then the fiber mats were pressed for either 5, 6 and 7 minutes. Eighteen combinations of variables were obtained and for each combination, three boards and a total of 54 were produced.  The anatomical characteristics of the roots and physical and mechanical properties of MDF including bending strength and modulus of elasticity, internal bonding and thickness swelling after 2 and 24 hours immersion in water were measured. The results revealed that the average fiber length and diameter of the root fibers were 1.02 mm and 11.63 µm respectively. The maximum bending strength , modulus of elasticity, internal bonding of the boards produced using fibers generated after 20 minutes steaming time, 7 minutes pressing and 10% resin were measured as 5.291 MPa. 559.4 MPa. and 0.1245 MPa., respectively. The minimum thickness swelling after 2 and 24 hours immersion in water of the above mentioned boards were 31.6% and 34.12% respectively. The results indicated that the fiber produced from licorice root can be used as a partial substitute in MDF production.